Development of A Chemoentrepreneurship Oriented Electronic Module (e-Module) On the Concept of Buffer Solutions - Wijayanti, Imas Eva; Febriyanti; Affifah, Isriyanti (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
Innovation in technology-based teaching materials is one of the innovations brought by technological advances in the 21st century in the field of education, one of which is module innovation in electronic form (e-module). However, millennial students currently don't really like learning science, one of which is chemistry because they think it's boring. This can be overcome by learning with a contextual approach, one of which is chemo-entrepreneurship in the form of electronic modules in buffer solution material. Through e-modules, students obtain information about chemical concepts in the processing of materials into chemical-based entrepreneurial products. The aim of this development research is to create a chemo-entrepreneurship oriented electronic module (e-module) based on the buffer solution concept. The ADDIE model which includes the stages of analysis, design, development, implementation and evaluation was used to plan this research. After going through validation by five material experts and media experts, this e-module was declared valid because the V value exceeded 0.80 in the Aiken's test. A total of 19 students of XI MIPA 4 SMA Negeri 8 Serang City were used for limited e-module testing and obtained a percentage of 92% in the very good category. Keywords: Electronic module (e-module), chemo-entrepreneurship, buffer solution, ADDIE